Respostas
respondido por:
0
a) (3x² + 2x - 1) + (- 2x² + 4x + 2) ⇒
3x² + 2x - 1 - 2x² + 4x + 2 ⇒
3x² - 2x² + 2x + 4x - 1 + 2 ⇒
x² + 6x + 1
b) (3a - 2b + c) + (- 6a - b - 2c) + (2a + 3b - c) ⇒
3a - 2b + c - 6a - b - 2c + 2a + 3b - c ⇒
3a - 6a + 2a - 2b - b + 3b + c - 2c - c ⇒
5a - 6a - 3b + 3b + c - 3c ⇒
- a + 0b - 2c
- a - 2c
3x² + 2x - 1 - 2x² + 4x + 2 ⇒
3x² - 2x² + 2x + 4x - 1 + 2 ⇒
x² + 6x + 1
b) (3a - 2b + c) + (- 6a - b - 2c) + (2a + 3b - c) ⇒
3a - 2b + c - 6a - b - 2c + 2a + 3b - c ⇒
3a - 6a + 2a - 2b - b + 3b + c - 2c - c ⇒
5a - 6a - 3b + 3b + c - 3c ⇒
- a + 0b - 2c
- a - 2c
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás